2016
DOI: 10.1093/femsle/fnw236
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficileenvironmental contamination within a clinical laundry facility in the USA

Abstract: Clostridium difficile is both a hospital and community acquired pathogen. The current study determined if C. difficile could be cultured from clinical laundry facility surfaces. A total of 240 surface samples were collected from dirty areas (n = 120), which handle soiled clinical linens, and from clean areas (n = 120), which process and fold the clean linens, within the University of Washington Consolidated Laundry facility in 2015. Sampling was done four times over the course of one year. The dirty area was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Therefore we proposed a low genetic diversity of toxigenic strains in Isfahan, Iran. Other similar studies in Europe, the Middle East, and North America previously identified ST2 as a common clinical strain all around the world [29]. Studies performed in China and France showed various STs in A − B + strains, yet the most prevalent STs were ST-2, ST-54, ST-37, and ST-35 in China and ST-1 in France.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore we proposed a low genetic diversity of toxigenic strains in Isfahan, Iran. Other similar studies in Europe, the Middle East, and North America previously identified ST2 as a common clinical strain all around the world [29]. Studies performed in China and France showed various STs in A − B + strains, yet the most prevalent STs were ST-2, ST-54, ST-37, and ST-35 in China and ST-1 in France.…”
Section: Discussionmentioning
confidence: 76%
“…1A), being the coexistence event 3 caused by Clade-1 and Clade-2 STs. Two of these events were identified from CO samples (events 2 and 3) and ST-8 was the only ST that was present consistently in all the events, which could be due to its widely reported frequency 25 . Although in Colombia typing schemes have been applied to a small number of isolates of C .…”
Section: Discussionmentioning
confidence: 93%
“…Also, handling dirty clothes and then sorting washed clothes can result in cross-contamination. This crosscontamination web has been reported in commercial laundries (41,42). Furthermore, on May 24, 2021 by guest http://aem.asm.org/ Downloaded from storage of the clothing can result in growth of bacteria and molds under humid conditions (28).…”
Section: Laundry Processingmentioning
confidence: 63%